CULTURABLE ENDOSYMBIOTIC BACTERIA FROM THE INDIAN LAC INSECT, KERRIA LACCA (KERR) - Verma, Sweta; Kumar, Hemant; Ramani, Ranganathan; Chandra, Ramesh (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
The Indian lac insect, Kerria lacca (Kerr) (Coccoidea: Tachardiidae) is a commercially important phytosuccivorous and sessile scale insect. Lac insects are cultured on suitable host plants in India and some Southeast Asian countries to produce lac. The lac insect harbours a number of endosymbionts. Isolation of culturable microbial endosymbionts and their identification through 16S rRNA has revealed sex and host-related differences of microbial species. Bacillus boroniphilus, Enterobacter cloacae and Staphylococcus sp. were found only in the lac insects reared on the plant host Cajanus cajan, whereas Bacillus firmus, Lysinibacillus xylanilyticus, Bacillus horneckiae and Bacillus velezensis were recorded only from Flemingia macrophylla. B. firmus and L. xylanilyticus were female-specific and B. horneckiae and B. velezensis were male-specific with Flemingia macrophylla as host; E. cloacae was female-specific and Bacillus boroniphilus and Staphylococcus sp. were male specific with C. cajan. Biochemical characteristics of the isolates, their genetic relationship with their taxonomic kin and their probable role, based on the information available about these endosymbionts in other hosts, have been studied.